Sustainable Islamic Development: An Empirically Derived Maqasid-Based Economic Governance Model in Pesantren - Ahmad Saef Alfath; Fauzan; M.F. Hidayatullah (CV. Tripe Konsultan, 2026)
The transformation of Islamic boarding schools (pesantren) into socio-economic institutions has increased their strategic role in promoting sustainable community development. However, previous studies have primarily emphasized economic outcomes while providing limited understanding of how economic governance is constructed through Islamic values. This study aims to analyze economic governance practices in pesantren, examine the internalization of Maqasid al-Shariah in institutional decision-making, and develop an empirically derived Maqasid-Based Economic Governance Model toward Sustainable Islamic Development. A qualitative multiple-case study design was employed involving two Indonesian pesantren with established economic institutions. Data were collected through in-depth interviews, participant observation, and institutional documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña combined with grounded theory coding procedures consisting of open, axial, and selective coding. The findings indicate that economic governance in pesantren is characterized by collective leadership, transparency, accountability, participation, effective business management, benefit distribution, and value-based decision-making. These governance practices are transformed through the internalization of the five dimensions of Maqasid al-Shariah Hifdz al-Din, Hifdz al-Nafs, Hifdz al-Aql, Hifdz al-Nasl, and Hifdz al-Mal which function as an operational governance mechanism rather than merely a welfare evaluation framework. The study proposes an empirically derived institutional model demonstrating that governance practices strengthen a sustainable pesantren economy and ultimately contribute to Sustainable Islamic Development. The findings extend Islamic development economics by integrating economic governance, maqasid internalization, and sustainability into a unified institutional framework that provides both theoretical advancement and practical guidance for strengthening value-based governance within pesantren.